Performance based design with semi active structural control technique. - Kurata, Narito (Earthquake engineering & structural dynamics.)
The recent spate of large earthquakes has triggered diverse performance requirements for structures. This has led to increasing worldwide interest in performance based design methods. To establish such methods, however, it is necessary to evaluate structure conditions after defining the loads, and this is difficult to accomplish. On the other hand, there has been steady progress on research and development of structural control techniques for improving structural performance. These technological innovations need to be rationally incorporated into structural design. In particular, semi active structural control techniques are effective in improving structural performance during large earthquakes. By effectively incorporating them into the design, it is possible to meet the various structural performance requirements. This paper first outlines the various structural control methods and focuses on the semi active structural control technique as the main topic. It then describes an example to verify the effectiveness of the semi active structural control technique in high rise buildings.